Pengaplikasian Sistem Validasi Tiket Digital Berbasis Qr Code Dengan Pengolahan Citra - Judistira, Wahyu Eka; Darmono, Rondi Sahputra; Azis, Khairul; Siregar, Rahmat Abdillah Nuh; S, Supiyandi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The use of QR code as a digital ticket has become widespread in various industries, including transportation, entertainment, and other services. While QR codes offer convenience and efficiency, digital ticket validation systems based on QR codes often face challenges in scanning accuracy, particularly under suboptimal image conditions, such as poor lighting or damage to the QR code. This study aims to develop a digital ticket validation system using QR codes by leveraging image processing techniques to enhance reading accuracy. Image processing technology is applied to improve the quality of QR code images before scanning, thus reducing detection errors that may occur under less-than-ideal conditions. The system implements algorithms based on edge detection, distortion correction, and contrast enhancement, significantly improving the performance of QR code scanning and validation under varying circumstances. The system was tested using a QR code dataset with different image quality levels, and results showed a 15% improvement in scanning accuracy compared to systems without image processing. This research is expected to contribute to the development of more efficient and reliable ticket validation systems and provide a foundation for further advancements in the field of QR code applications and image processing (Feng & Xie, 2018; Wang & Chen, 2023).